Vection and visually induced motion sickness: how are they related? - Keshavarz, Behrang; Riecke, Bernhard E.; Hettinger, Lawrence J.; Campos, Jennifer L. (Frontiers in Psychology, 2015)
The occurrence of visually induced motion sickness has been frequently linked to the sensation of illusory self-motion (so-called vection), however, the precise nature of this relationship is still not fully understood. To date, it is still a matter of debate whether or not vection is a necessary prerequisite for visually induced motion sickness (VIMS). That is, can there be visually induced motion sickness without any sensation of self-motion? In this paper, we will describe the possible nature of this relationship, review the literature that may speak to this relationship (including theoretical accounts of vection and VIMS), and offer suggestions with respect to operationally defining and reporting these phenomena in future.